Growth Strategy for Kampung Sumber Alam Hot Spring Resort - Pratama, Putra Samodra; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2012)
The tourism industry is predicted to become one of the biggest industries in the world with estimation of total expenditure of USD 2.000 billion in 2020. As for Indonesia, the number of domestic tourist visits have reach 1,9 billion and 6,63 billion for international tourist visits. Garut as one of the Indonesiaâ€™s tourist attraction also experience this increasing number with Cipanas hot spring attraction as the significant contributor. Kampung Sumber Alam Hot Spring Resort (KSA) is a hot spring resort in Cipanas with 25 years of experience in the industry and has been the market leader since.The business performance of KSA has been good for the last many years in the term of market position and profit. But now with the growing condition of the industry will make the industry become more attractive and make the environment and industry will keep changing in the term of the markets, consumers, and especially the competitors. This condition makes KSA need to think about strategies for the future in order to maintain its market position while at the same time seizing the opportunities of the growth of the industry.The focus of this final project is to find strategies solutions that would able to help KSA to grow in the future so that it can deal with the changing environment and industry conditions while at the same time seizing the opportunities.To respond to these conditions some strategy recommendations are proposed. The generating process of the strategies is using literature study method. The strategies that generated are Corporate Strategy- Growth Strategy, SPACE Matrix, Innovation Strategy, Creative-based Tourism, Eco-tourism, Customer Service Strategy â€“ Human Resource Strategy, and Pause/ Proceed with Caution Strategy. Keywords: tourism, hospitality industry, Cipanas, Garut, hot spring resort, growth strategy.Â